Identification method and distribution of palaeovolcanoes in Mulei Depression in the Junggar Basin, Western China. (5th September 2019) - Yang, Xiaoguang; Guo, Shaobin; Liu, Zhen
Abstract : The Mulei Depression is a secondary structural unit in the south‐eastern part of the Junggar Basin in the Central Asian Orogenic Belt. As in other parts of the Junggar Basin, it experienced large‐scale volcanic activity in the Carboniferous. However, due to the seismic data, quality of this area is poor, and the drilling data is less early, the Carboniferous volcanic activity is difficult to identify and explain. In the case of minimal well information available, we identify the volcanoes of the Upper Carboniferous Bashan Formation of the Mulei Depression and clarify its distribution characteristics. Through frequency decomposition and a reconstruction of seismic data, the seismic reflection characteristics of the ancient volcanic cone become prominent and easy to identify, and even the period of some stacked volcanic cones can be divided. According to the geological model put forward, the seismic reflection characteristics of the ancient volcanic cone and its surrounding volcanic rocks are clarified. The volcanic cones are characterized by mound‐clutter and weak‐blank amplitude reflection. The internal clutter mainly have resulted from rapid changes in lithology and complex secondary faults. Away from the crater direction, the energy of a seismic event is gradually enhanced, and the volcanic sediments from other sources will be superimposed above the previously formed volcanoes. It is found that the volcanic channel with a short‐axis continuous illusion is often developed at the bottom. The volcanic channel which can be identified in seismic mainly affects the development of large volcanoes. Finally, 27 volcanic cones and seven volcanic channels were identified via establishing the three‐dimensional (3D) model of the volcano and the amplitude of the root mean square of seismic data after reconstruction, as well as interpreting deep faults. The volcanic development in the Mulei Depression has the characteristics of an NE spread along deep faults and northern more than southern.